2022
DOI: 10.3389/fpubh.2022.904792
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Half of Women Have Experienced Intimate Partner Violence During Pregnancy in Northwest Ethiopia, 2021; The Role of Social Support and Decision-Making Power

Abstract: BackgroundIn developing countries, intimate partner violence is increasing alarmingly, though attention to this issue is rarely given. It has devastating effects on the general wellbeing of women, pregnancy outcomes, and the long-term health of children, and this needs to be addressed. Hence, this study was designed to assess intimate partner violence and associated factors in northwest Ethiopia.MethodsA community-based cross-sectional study was conducted from July 1st to August 30th, 2021, among 858 postpartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Prevalence of IPV is lower than the pooled magnitude reported in different parts of Ethiopian and in East Africa (9,13,23,24). This might be attributed to two studies are based on demographic and health survey data which include emotion/physiological violence while this study entertains only Physical and/or sexual IPV.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Prevalence of IPV is lower than the pooled magnitude reported in different parts of Ethiopian and in East Africa (9,13,23,24). This might be attributed to two studies are based on demographic and health survey data which include emotion/physiological violence while this study entertains only Physical and/or sexual IPV.…”
Section: Discussionmentioning
confidence: 73%
“…In Africa its prevalence ranges from 2% to 57%, with an average overall prevalence of 15.23% (5,8). In Ethiopia, one in three women of reproductive age group experienced at least one form of physical and/or sexual violence (2), and nearly half of women experience IPV during pregnancy in North West Ethiopia (9). IPV in Ethiopia ranged from 12% in Yirgalem (10) to 44.7% Abay Chome district (11), with an average prevalence of 26.1% nationally (12).…”
Section: Introductionmentioning
confidence: 99%
“…Couple sociodemographic characteristics were not found signi cant in this study while previous studies reported a nding like this study and an association report with IPV as well. Like studies (9,35) age of the respondent is not found signi cant while studies (13,24,(36)(37)(38) reported that advanced respondent age and lower to middle wealth index were found to increase the odds of IPV. In line with studies (23,35) respondent educational status is not found signi cantly affecting IPV, while studies (9,13,16,37) reported that no formal education was found to increase the odds of IPV.…”
Section: Discussionmentioning
confidence: 84%
“…Like studies (9,35) age of the respondent is not found signi cant while studies (13,24,(36)(37)(38) reported that advanced respondent age and lower to middle wealth index were found to increase the odds of IPV. In line with studies (23,35) respondent educational status is not found signi cantly affecting IPV, while studies (9,13,16,37) reported that no formal education was found to increase the odds of IPV. In this study husband educational status and age does not show signi cant association with IPV while studies (27,39) reported that husband better educational status lowers odds of IPV and other studies (13,23,37) reported that no or primary husband educational attainment increased the odds of IPV.…”
Section: Discussionmentioning
confidence: 84%
“…Women sociodemographic characteristics were not found signi cant in this study while previous studies reported a nding like this study and an association report with IPV as well. Like studies (9,35) age of the respondent is not found signi cant while studies (13,24,(36)(37)(38) reported that advanced respondent age and lower to middle wealth index were found to increase the odds of IPV. In line with studies (23,35) respondent educational status is not found signi cantly affecting IPV, while studies (9, 13, 16, and 37) reported that no formal education was found to increase the odds of IPV.…”
Section: Discussionmentioning
confidence: 84%